Changes in Turkish Budget System: Transition to Performance-Based Program Budgeting - Ezgim Yavuz; Hüseyin Burak Özgül; Nazan Susam (Maliye Çalışmaları Dergisi)
Due to its economic functions, including that of a planning strategy for the future, state budget as a management tool requires the transition from a traditional structure to a modern one. In the modern budget systems principally implemented today, effectiveness and the efficiency of the results are taken into consideration rather than the cost of the services provided by the state. Although there are various types of modern budget systems, program budget and performance-based budget systems have been implemented in Turkey. Modern budget systems were put into practice in order to change the input-oriented structure of the classicalbudget. However, structural problems and the inability to measure the outputs at the desired level have resulted in the budget systems going back to the traditional structure. The aim of this study is to evaluate the changes in the methods applied, legal and institutional structure of the Turkish budget system and the problems that have emerged, starting with the General Accounting Law No. 1050 and until today.